1999
DOI: 10.1093/ptj/79.12.1177
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Extremity Muscle Force and Balance Performance in Adults Aged 65 Years and Older

Abstract: Background and Purpose.Measures of postural control may be useful for determining fall risk in older people and for determining the outcomes of treatments aimed at improving balance. Commonly used tools measure the output of the postural control system. The purpose of this study was to determine the degree to which one component of postural control (muscle force) contributes to scores on 3 functional balance measures. Subjects. Fifty community-dwelling volunteers between 65 and 91 years of age (X̄=74.82, SD=6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(96 citation statements)
references
References 21 publications
4
78
1
10
Order By: Relevance
“…The distance was measured (in cm) on a tape measure fixed to a wall. Daubney and Culham (1999) reported for this test strong intrarater reliability (r ¼ 0.92) and test-retest reliability (r ¼ 0.98). FRT measurements were taken for experimental and control groups before and after the strength-training program.…”
Section: Functional Tasksmentioning
confidence: 71%
“…The distance was measured (in cm) on a tape measure fixed to a wall. Daubney and Culham (1999) reported for this test strong intrarater reliability (r ¼ 0.92) and test-retest reliability (r ¼ 0.98). FRT measurements were taken for experimental and control groups before and after the strength-training program.…”
Section: Functional Tasksmentioning
confidence: 71%
“…As Daubney et al tested, the ankle dorsiflexors were found to be the best predictor of falling. 39 During gait, the ankle dorsiflexors are involved, together with the hip and knee flexors, in lifting the lower limb during the swing phase to make sufficient clearance of the toes over the ground to prevent tripping. Taken together, lower extremity muscle strength may be an important predisposing factor in the pathogenesis of falls.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Diminished ability to maintain balance is associated with fear of falling and risk of falling. 4 Physiological changes related to aging, for example, in cognitive function, 5 muscle strength, 6,7 lack of proprioception, 8 joint range of motion, 9 reaction time, 10 and sensory systems 11 may negatively affect balance control and affect the functional ability of older adults. Central nervous system (CNS) medications-hypnotics in particular [12][13][14] -have also been implicated as strong factors affecting balance and falls in older adults.…”
mentioning
confidence: 99%